Effect of microwave irradiation on secondary structure of α-amylase by circular dichroism - Zhang, Xiao-yun; Qin, Wen-qing; Tian, Xue-da; Huang, Meng (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2011)
Based on the starch hydrolysis reaction accelerated by microwave irradiation with α -amylase, the circular dichroism (CD) and secondary structure changes of α -amylase under the condition of microwave irradiation and water bath were studied by circular dichroism spectra. The results showed that, both the peak heights (at λ =193 nm) of the CD spectra of the samples treated by microwave irradiation and water bath reduced. The reduced rate by microwave irradiation ranged from 140% to 220%, while the reduced rate by water bath ranged from 60% to 140%. The peak of the sample treated by microwave irradiation for 60 min disappeared at λ =193 nm, while the sample showed a wake peak by water bath. The peak position by microwave irradiation emerged a blue shift in the range of 5–8 nm at λ =204 nm and λ =220 nm, while it emerged in the range of 3–5 nm by water bath. With time going on, the microwave irradiation and water bath have prompted the secondary structure of α -helix, β -sheet, β -turn and the mutual transformations of random coil, but the trends were different.